2018
DOI: 10.15537/smj.2018.9.22668
|View full text |Cite
|
Sign up to set email alerts
|

Women’s perception and attitude to medical students’ participation in obstetrics and gynecology care

Abstract: Objectives:To determine the attitudes of obstetric and gynecological patients towards medical students’ participation in clinical care.Methods:Patients in an obstetric and gynecological practice in Kingdom of Saudi Arabia, completed a structured self-administered online questionnaire to assess demographic, reproductive and lifestyle variables that affected their attitude towards the acceptance of medical students’ participation in outpatient clinical care.Results:Out of the 595 women surveyed, 64.7% received p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
0
11
0
3
Order By: Relevance
“…28 , 29 In addition, one study of Saudi Arabian women seeking OB-GYN care showed that they were more comfortable in the presence of female medical students, especially when pelvic examination was indicated, and the presence of male medical students increased the levels of patient discomfort. 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 , 29 In addition, one study of Saudi Arabian women seeking OB-GYN care showed that they were more comfortable in the presence of female medical students, especially when pelvic examination was indicated, and the presence of male medical students increased the levels of patient discomfort. 30 …”
Section: Discussionmentioning
confidence: 99%
“…28,29 In addition, one study of Saudi Arabian women seeking OB-GYN care showed that they were more comfortable in the presence of female medical students, especially when pelvic examination was indicated, and the presence of male medical students increased the levels of patient discomfort. 30 The study's strengths include a high response rate and a high degree of internal and external data consistency. Limitations are primarily due to those inherent in crosssectional surveys and use of a single academic care center site, which may constrain the generalizability of study findings.…”
mentioning
confidence: 99%
“…Several studies, including ours, found that participants felt more at ease with female students than with male students (Salah et al, 2015;Subki et al, 2018). Chang et al (2010) reported that male students were refused by patients to participate in clinical interviews and physical examinations, including pelvic examinations.…”
Section: Discussionmentioning
confidence: 80%
“…Like other literature (Nicum & Karoo, 1998), medical students also provided patients with useful medical information and support. Furthermore, patients strongly supported the idea that real patient encounters and practices under clinical supervision are more effective methods for improving student's clinical skills than just mere observation or skill laboratory practice (Subki et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…However, their gynaecological patients were more accepting of medical students than obstetric patients. 14 Studies conducted elsewhere reported that male students are denied consent to perform pelvic examination more often by clinic patients than by private patients. 15,16 None of our participants are private patients.…”
Section: Discussionmentioning
confidence: 99%